Perlindungan Hukum Terhadap Korban Tindak Pidana Perdagangan Orang Dalam Sistem Peradilan Pidana di Indonesia Berdasarkan UndangUndang Nomor 21 Tahun 2007 tentang Tindak pidana Perdagangan Orang (Studi Kasus Putusan Nomor 207k/Pid.Sus/2017 dan Putusan Nom - Almusa, Aldi; Ajie Wicaksono, Bintang (Postulat, 2025)
This research examines and reviews. 21 of 2007 and the legal protections for trafficking victims within Indonesia's criminal justice system are investigated in this research. How victims are protected by the law and how well the law is applied are the study's main concerns. Qualitative data analysis from primary and secondary sources is combined with an empirical and normative legal approach in this research methodology. The findings of the research show that Law No. 21 of 2007 has controlled victims' rights to bodily and psychological protection, rehabilitation, and social reintegration, as well as complete protection. The apparatus's capacity limitations, inter-institution coordination issues, and the stigma associated with victims still limit how successful its implementation may be. For legal protection to function as best it can and provide victims justice, it is thus essential to enhance implementation and cross-sector assistance.